Combined and Modified Gibson and Ilioinguinal Approaches in Type II + III Internal Hemipelvectomy for Periacetabular Tumors - Hu, Xin; Lu, Minxun; Wang, Jie; Li, Longqing; Min, Li; Tu, Chongqi (Frontiers in Oncology, 2022)
Abstract Backgroud: The routine iliofemoral approach and its modifications in type II+III resection require extensive skin incision and massive periacetabular muscle detachment, leading to prolonged hospital stay, increased complication incidence, and impaired lower limb function. Under the management of an enhanced recovery after surgery (ERAS) protocol, a combined and modified Gibson and ilioinguinal (MGMII) approach was used to avoid unnecessary soft tissue trauma during tumor resection, and therefore advantage patients’ return to normal life. Methods: 25 patients with type II + III (including type II) periacetabular tumors who underwent reconstruction with 3D printed customized endoprostheses at our center between January 2017 and March 2019 were included in this study. There were 13 cases using MGMII approach and 12 cases using iliofemoral approach. The operation duration and blood loss were assessed by chart review. The surgical margin was evaluated by the histopathological studies. The reconstruction accuracy, the abductor muscle strength, the 1993 version of the Musculoskeletal Tumor Society (MSTS-93), the Harris Hip scores (HHS), and the limp score was evaluated. Complications were recorded after reviewing the patients’ records. Results: The operative duration and blood loss in MGMII group were shorter than those in iliofemoral group, but the postoperative hemoglobin was slightly higher than that in the iliofemoral group. The MGMII group had stronger postoperatively hip abductors, better functional restoration, and relatively fewer patients with higher limp scores. No complication was observed in MGMII group. In iliofemoral group, three patients encountered wound healing delay and one patient occurred deep infection. Conclusions: The MGMII approach can better expose the posterior column of the acetabulum, especially the ischial tuberosity, which is beneficial for avoiding tumor rupture during resection. The MGMII approach also helps to preserve residual muscle function, such as the origin of the gluteus medius, while ensuring the extent of resection.